Perhitungan Volume dan Sebaran Sedimentasi Waduk Sermo Berdasarkan Kondisi Awal Pembangunan dan Keadaan Terkini di Tahun 2016 - Cahyono, Bambang Kun (2017)
Sermo Dam was built in the Hargowilis village, Kokap, Kulonprogo, DI Yogyakarta. The Dam is blocking river’s water flow of the Ngerancah river and several rivers in this area. It fills certain part of Hargowilis area with approximately 25 million cubic meters fresh water. Because of the water potential and side view of the area, Sermo dam was developed to various beneficial function such as irrigation, fresh water needs for surrounding area, flooding and drying control, and tourism. Due to this mentioned functions, therefore good management and maintenance for the dam is needed. One of the problems that can not be avoided be cause of blocking rivers flow is sedimentation. If the sedimentation is uncontroled it will fill up the dam, and will reduce water storage capacity of the dam. To control the sedimentation, so some measurements must be executed to know the current condition and the acceleration of sedimentation. It is necessary to measure the volume of water storage and predict the sedimentation rate. This paper trying to determine volume of Sermo Dam water storage in 2016, and predict Sermo Dam sedimentation rate since it was first built (1996) to the present (2016). Based on resulted data it can be analysis using geospatial based data analysis, the volume of Sermo Dam water storage is 13,153,894.056 cubic meters (water level at 130 meter), and the rate of sedimentation acceleration in Sermo Dam is 184,569.687m3/year. In addition, spread of sedimentation patterns also served in the distribution map and profile changes of sedimentation